2002
DOI: 10.1258/0022215021911248
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between bacteriology of the middle meatus and ethmoid sinus in chronic sinusitis

Abstract: In this study we report on the correlation between the bacteriology of the middle meatus and ethmoid sinus in chronic sinusitis. When patients with chronic sinusitis underwent functional endoscopic sinus surgery (FESS), swab specimens were taken from the middle meati before surgery. After removing the ethmoid bullae, swab specimens were taken from the ethmoid sinuses. Between November 1998 and February 2001, 186 pairs of middle meatal and ethmoid sinus specimens were collected from 186 patients. No bacteria we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 14 publications
(26 reference statements)
1
20
0
2
Order By: Relevance
“…As briefly discussed above, multiple factors could influence the microbiome studies that include, but are not limited to, regional variations of the microbiome (nasal cavity vs. sinuses) [98],[37], antimicrobial use around the time of sampling [53, 99], sampling methods (lavage, tissue biopsy, swab etc. ), disease subgroups [54], age [65], severity and phenotypes of included cases or genetic background of patients.…”
Section: Analyzing the Sino-nasal Microbiome: The Disparity And The Cmentioning
confidence: 99%
“…As briefly discussed above, multiple factors could influence the microbiome studies that include, but are not limited to, regional variations of the microbiome (nasal cavity vs. sinuses) [98],[37], antimicrobial use around the time of sampling [53, 99], sampling methods (lavage, tissue biopsy, swab etc. ), disease subgroups [54], age [65], severity and phenotypes of included cases or genetic background of patients.…”
Section: Analyzing the Sino-nasal Microbiome: The Disparity And The Cmentioning
confidence: 99%
“…Las causas de esto pueden incluir: factores técnicos como contaminación de la muestra, inadecuada técnica de sembrado, así como un medio de cultivo no adecuado para anaerobios estrictos que podrían haber disminuido el número de anaerobios estrictos aislados en nuestro estudio y el tratamiento con corticoesteroides nasales que se administra a los pacientes, que aumenta el drenaje de material purulento y permite una mejor oxigenación de los senos paranasales disminuyendo el crecimiento de anaerobios. 2,5,[7][8]13 También se estudió la incidencia de hongos en nuestros pacientes con rinosinusitis crónica e inmunodeficiencia común variable. Dos muestras tuvieron desarrollo de Candida albicans (8%) y una muestra de Aspergillus fumigatus (4%), cifras menores a las reportadas por Araujo 4 Esto sugiere que a todos nuestros pacientes con diagnóstico de rinosinusitis crónica e inmunodeficiencia común variable debemos tomar cultivo de secreción del meato medio vía endoscópica, para iniciar el tratamiento adecuado principalmente contra Staphylococcus aureus y Moraxella catarrhalis.…”
Section: Discussionunclassified
“…Establecieron el uso de aspiración de meato medio como el mejor método para identificar los microorganismos en pacientes con diagnóstico de rinosinusitis crónica. 7,8 Araujo y colaboradores demostraron que 80% de las muestras obtenidas por punción del seno maxilar y las obtenidas por secreción de meato medio tenían crecimiento del mismo microorganismo. Este estudio sugiere que el cultivo obtenido guiado por endoscopia del meato medio es una alternativa viable y eficiente en relación con la punción del antro maxilar, tiene las ventajas de ser un método no invasivo y menos costoso.…”
Section: Antecedentesunclassified
“…Seven studies of patients with CRS performed since 1991 are shown in Table 5. [57][58][59][60][61][62][63] Three studies were prospective. The importance of a prospective investigation is that there is more assurance that patients are identified and cultures are processed in a standard fashion.…”
Section: Bacterial Infection Summary Statementsmentioning
confidence: 99%